A Literature Review on Blue Brain - Chauhan, Neeraj; Singhania, Gaurav; Pandey, Amit (International Journal of Engineering and Technology, 2018)
Human Brain is the most complicated creature on earth that will be demolished after certain decay of years. This research paper is based on the theoritical concept -”How its intelligence can be preserved for future use and what methodology is used for preserving it. It also dicussed about its merits, demerits and lots of other things that we can do with it.
Keywords: Blue Brain; nanobots; central nervous system; virtual brain; artificial intelligence; blue gene; neural networks; axons; dendrites and sensory cells.